Transparansi Laporan Pertanggungjawaban Dana Bantuan Operasional Sekolah pada Sekolah Dasar Islamiyah 1 Kota Ternate - Kurupunda, Muhaimin L. Hi; Fatmawati, Fatmawati; Sudarmi, Sudarmi (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
the aims of this research is to determine the implementation of transparency of accountability report school operational assistance at SD Islamiyah 1 in Ternate. The method of this research is qualitative research. The data was collected through observation, interview and documentation. The object of this research is SD Islamiyah 1 Ternate and the subject of this research were headmaster, treasurer, committee chairman and student guardian.The result of this research shows that the implementation of  the principle of transparency in the accountability report for school operational assistance funds (BOS) at SD Islamiyah 1 Ternate City has been going well. There are three indicators in this research, namely the legal framework, independent and effective audits, and community involvement. SD Islamiyah 1 Ternate City carries out the budgeting process from planning to realization in an open and truly accountable manner. The management of BOS funds is carried out by using technical guidelines (JUKNIS) as the basis so that BOS funds can be used effectively.